Curcumin Protects Human Umbilical Vein Endothelial Cells against H2O2-Induced Cell Injury - Jipeng Ouyang; Rong Li; Haiqin Shi; Jianping Zhong (Pain Research and Management)
Migraine is a prevalent neurological disorder which causes a huge economic burden on society. It is thought to be a neurovascular disease with oxidative stress might be involved. Curcumin, one of the major ingredients of turmeric, has potent antioxidative and anti-inflammatory properties, but whether it could be used as a potential treatment for migraine remains to be explored. In the present study, human umbilical vein endothelial cells (HUVECs) were pretreated with various concentrations of curcumin (0 μM, 10 μM, 20 μM, 30 μM, 40 μM, and 50 μM) for 12 h, thereby exposed to H2O2 (100 μM) for another 12 h. The viability of HUVECs was tested by the CCK-8 assay, and the activities of antioxidant enzymes including superoxide dismutase (SOD) and glutathione (GSH) were also examined. Intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) were assayed to determine H2O2-induced oxidative stress. In addition, several cell death-related genes (p53, p21, Bax, and Bcl-2) were detected by PCR, and an apoptosis-related protein (caspase3) was evaluated by western blotting. Our results showed that curcumin improved the H2O2-induced decrease of cell viability and antioxidative enzyme activities and decreased the level of oxidative stress. As a conclusion, curcumin could mitigate H2O2-induced oxidative stress and cell death in HUVECs and may be a potential therapeutic drug for migraine.